THE IMPORTANCE OF TRANSPORT TECHNOLOGY PROFESSIONALS` TRAINING THROUGH THE PRISM OF THEIR STATUS IN THE UKRAINIAN LABOUR MARKET - Lebid, Iryna (Proceedings of National Aviation University, 2020)
The article is focused on the rationale behind transport technology professionals` training evaluating the current workforce situation in the market for transport and logistics services in Ukraine. The aim of the paper is to assess economic reasons for transport technology professionals` training through the analysis of these specialists` status in Ukraine`s labour market according to the following parameters: the average number of employees by the lines of business per quarter, workforce movement, the number of workers who were forcedly put on short time, full-time employees` average monthly wages in 2019. The methods used are the system-structural analysis, systematization, comparison and generalization of the relevant sources. The obtained results lie in the fact that in Ukraine there is a controversy between the actual needs of the economy for transport professionals, the economic potential the transport sector is characterized by, and the actual number of professionals, negative labour movement tendencies and low compensation received in the transport sector. The discussion points are centered around the reasons for this happening – the overall level of Ukraine`s economic development, a lack of interest in the field or a lack of awareness of prospects of the industry as well as transportation and logistics functions. A conclusion is made on a number of important steps to be taken to improve the situation.